Потери от уравнительных токов в многожильных обмотках беспазовых электрических машин - Антонов, А.Е.; Киреев, В.Г.; Петухов, И.С. (Технічна електродинаміка, 2011)
The mechanism of electric power losses from misbalanced currents in multi-stranded winding of slotless permanent magnet electric machine is determined. The model of coils displacement during manufacturing causing inequality of the coil’s EDS is proposed. The method for estimation of the losses from misbalanced currents is developed and the factors, influencing on its value, are specified. The dependence of relative value of the losses on the number of winding coils is given. It is shown that the ratio of the losses from misbalanced currents to electromagnetic power of the electric machine does not depends on the value of magnetic induction and rotation frequency of rotor.